Pathophysiology, prevention, and management of coronary microvascular obstruction - Cenko, Edina; Badimon, Lina; Vadalà, Giuseppe; Merkus, Daphne; Antoniades, Charalambos; Collet, Carlos; De Maria, Giovanni Luigi; Djordjevic-Dikic, Ana; Drenjancevic, Ines; Escaned, Javier; Ferreiro, José Luis; Fleming, Ingrid; et al. (Oxford University Press (OUP), 2026)
Abstract Although prompt primary percutaneous coronary intervention (PCI) reduces mortality in patients with ST-elevation myocardial infarction (STEMI), the burden of post-infarction heart failure remains considerable and is expected to increase. A major contributory factor is suboptimal myocardial reperfusion, which persists in up to 60% of cases even with timely revascularization. This is largely driven by microvascular obstruction and ischaemia–reperfusion injury, culminating in the no-reflow phenomenon, a critical prognostic factor associated with impaired infarct healing, adverse left ventricular remodelling, and increased risk of heart failure and death. No-reflow is a complex and heterogeneous phenomenon, identifiable through different invasive and noninvasive technologies. When observed post-PCI, after excluding residual epicardial stenosis, it indicates poor microvascular perfusion and necessitates urgent management. Identifying patients at high risk and implementing early targeted interventions are essential to improving outcomes. Pharmacological therapies, including intracoronary adenosine and nitroprusside, have shown unclear benefit in improving microvascular flow. Non-pharmacological strategies, such as ischaemic postconditioning, intracoronary supersaturated oxygen therapy, stent-retriever thrombectomy, and mechanical left ventricular unloading, have demonstrated promise but require further validation in large-scale clinical trials. This clinical consensus statement summarizes current strategies for the prevention and treatment of no-reflow and underscores the need for improved risk stratification and novel microvasculature-targeted therapies. Addressing this persistent and significant unmet clinical need is crucial for improving care for STEMI patients and for mitigating its long-term complications, including heart failure and mortality.
Keywords: coronary no-reflow phenomenon; microvascular injury; microvascular obstruction; intramyocardial haemorrhage; ischemia-reperfusion injury; distal embolization; interstitial oedema; ST-segment elevation myocardial infarction; percutaneous coronary intervention; coronary blood flow; index of microcirculatory resistance; prognosis